Altered Mucosal Immune-Microbiota Interactions in Familial Adenomatous Polyposis. Issue 7 (16th July 2022) - Noble, Alistair; Durant, Lydia; Dilke, Stella M.; Man, Ripple; Martin, Isabel; Patel, Roshani; Hoyles, Lesley; Pring, Edward T.; Latchford, Andrew; Clark, Susan K.; Carding, Simon R.; Knight, Stella C.
Abstract : INTRODUCTION: Familial adenomatous polyposis (FAP) is a condition caused by a constitutional pathogenic variant of the adenomatous polyposis coli gene that results in intestinal adenoma formation and colorectal cancer, necessitating pre-emptive colectomy. We sought to examine interaction between the mucosal immune system and commensal bacteria in FAP to test for immune dysfunction that might accelerate tumorigenesis. METHODS: Colonic biopsies were obtained from macroscopically normal mucosal tissue from 14 healthy donors and 13 patients with FAP during endoscopy or from surgical specimens. Intraepithelial and lamina propria lymphocytes were phenotyped. Intraepithelial microbes were labeled with anti-IgA/IgG and analyzed by flow cytometry. RESULTS: Proportions of resident memory CD103-expressing CD8 + and γδ T-cell receptor + intraepithelial lymphocytes were dramatically reduced in both the left and right colon of patients with FAP compared with healthy controls. In lamina propria, T cells expressed less CD103, and CD4 + CD103 + cells expressed less CD73 ectonucleotidase. IgA coating of epithelia-associated bacteria, IgA + peripheral B cells, and CD4 T-cell memory responses to commensal bacteria were increased in FAP. DISCUSSION: Loss of resident memory T cells and γδ T cells in mucosal tissue of patients with FAP accompanies intestinal microbial dysbiosis previously reported in this precancerous state and suggests impaired cellular immunity and tumor surveillance. This may lead to barrier dysfunction, possible loss of regulatory T-cell function, and excess IgA antibody secretion. Our data are the first to implicate mucosal immune dysfunction as a contributing factor in this genetically driven disease and identify potentially critical pathways in the etiology of CRC.